The effect of lyophilisation on the physiochemical and biological properties of plant-based chitosan modified- poly lactic-co-glycolic acid microparticles - A.M. N. Shatri; Y. Lemmer; D.R. Mumbengegwi (The Microbe)
Terminalia sericea, Lantana camara, Grewiatenax, and Corchorus tridens extracts are potent against gastrointestinal bacteria. However, metabolism by gastric acid reduces their efficacy and limits their mainstream uses. Encapsulating extracts into microparticles could improve biological properties while offering protection against gastric acid. Moreover, lyophilizing microparticle suspensions could reduce swelling and bursting, while improving microparticle stability during long-term solid storage. The study aimed to investigate the effect of lyophilization on the physicochemical and biological properties of plant-based chitosan-modified-PLGA (CMPLGA) microparticles over time. The formulated microparticles were lyophilized and analyzed for size, polydispersity index, zeta potential, and pH. The antibacterial and cytotoxicity of the lyophilized microparticles were also determined by agar disc diffusion and MTT. There was a significant increase in microparticle size after lyophilization due to aggregation. However, there was no statistically significant change in zeta potential and polydispersity index after lyophilization p < 0.05. Potent antibacterial activity of the micro-dissolutions was recorded against clinical Salmonella and Verotoxigenic Escherichia coli with the lowest recorded Minimum inhibitory concentrations of 6.25 ± 0.0 µg/ml with only minimal microparticle swelling and leakage. CMPLGA microparticles containing L. camara showed the lowest IC50 of 66.7 ± 0.005 µg/ml, indicating that microparticles are not significantly toxic to the NIH/3T3 mouse embryonic cells. The study indicates that lyophilization could be a useful method for long storage of CMPLGA microparticles as it does not preserve the surface charges and polydispersity index of the nanoparticles, while enhancing the efficacy and safety of the CMPLGA nanoparticles.